Synthesizing of NiAl intermetallic Alloy as Hydrogen Storage by Arc Furnace Casting process - Haga, Gren
World demand on fossil fuel, especially in the transportation sector, triggers the research of alternative energy such as hydrogen has increased since 2002. Nowadays, hydrogen as a source of energy is still be avoided because of the high safety standard and large amount investation. The objective of hydrogen storage research is to reach the US DOE target of 2015 that synthezise reversible storage with up to 6 wt% capacity, more than 500 cycles,and can be used at atmospherice condition. This research was aimed to develop NiAl intermetallic alloy that can be used as hydrogenation storage, understanding the mechanism of hydrogen absorption and adsorption of metal and determining hydrogen absorption capacity of NiAl alloy. Methodology of this research consist of melting the NiAl alloy in an arc melting furnace followed by grinding the ingot into powder in a mechanical milling machine. Hydrogen absorption experiments was conducted at a temperature of 350°C in a sievert’s system developed by the researchers in PTBN Serpong. Hydrogen absorption capacity in specimen are measured by calculating the different pressure before and after hydrogenation. The result of hydrogen content that reaches 4.314 wt % cannot be used as a valid data because the system has not been calibrated. From SEM result, the particles of hydrogenated samples are dilated and also deagglomerated due to hydrogen pressure. Refinement result of XRD showed that none of NiAlH4 hydride formed and just a broader peak showed. Thermal Characterization with DTA showed the exothermal peak at temperature 150°C and 400°C and so can be concluded that Hydrogen is only adsorbed at the surface of the alloy physically but not chemically diffused in the lattice parameter so the hydride didn’t occur after hydriding process.